Obesity in the geriatric population - a global health perspective - Malenfant, Jason H; Batsis, John A (Journal of global health reports, 2019)
The obesity crisis has been a major concern for public health organizations worldwide, and affects the geriatric population in parallel to that of the general population. Though geriatric obesity has been recognized in developed countries, such trends have also extended into developing countries due to disproportionate consumption of energy-dense low-cost food and increasingly sedentary lifestyles. The consequences of geriatric obesity include impaired physical function, decreased quality of life, institutionalization and death. The aim is to describe the obesity epidemic in both developed and developing countries, as well as highlight current surveillance efforts to monitor geriatric obesity on a global scale such as the Study on Global Ageing and Adult Health (SAGE study), which evaluates epidemiology trends in six different countries (China, Ghana, India, Mexico, Russia and South Africa). The impact of obesity on health, disease and systems worldwide will be described, as well as projections of future trends of this disease.